'The Day the Dragon Licks Its Flank, You'll Find Us at Your Side': Self-Heroization and Revolutionary Organization. (3rd July 2022) - van Ree, Erik
ABSTRACT: This article argues that people locked in extreme conditions involving life-and-death risks on a long-term basis, often undergo a process of 'self-heroization'. Self-heroization includes the adoption of a heroic ethos and of an 'epic consciousness', i.e. people come to experience themselves as heroes living out an epic they themselves 'write' through their actions. The process will be explored at the hand of modern armed-struggle revolutionaries. Four closely entangled mechanisms will be explored. First, cognitively, the revolutionaries' heroic self-understanding reflects their violent and high-risk (heroic) lifestyle. Second, the modern revolutionaries' heroic ethos (a hybrid of courage and sacrifice; knowledge; and organization) emotionally endows them with a fighting spirit that allows them to perform their violent work. Third, self-heroization helps revolutionaries coping with their physically and existentially challenged, uprooted lives, by forging a sense of a higher, more glorious personality. And fourth, the adoption of an epic consciousness helps revolutionaries, who are mostly the weaker party in the conflict with the state, in boosting themselves for victory.